Physico-Chemical Features of Kali River, Karwar,West Coast of India - V. Khajure; J.L. Rathod, Gangadhar B. Kapsikar, Pradeep (Recent Research in Science and Technology, 2011)
The present study was carried out for the physico-chemical characteristics of a Kali river from October 2009 to March 2010. The parameters in this study ranged between Air temp., 12.7°C to 25.3°C; Water temp.11.3°C to 19.6°C; Transparency 52.6 cm.to 76.8 cm; Turbidity 14.4 JTU to 20.7 JTU; pH 7.1 to 8.3; Total solids 492.87 mg/I; Free co2 0.98 to 9.6 mg/I; Dissolved oxygen 9.66 mg/I to 11.75 mg/I; BOD 1.20 mg/I to 4.42 mg/I and chlorides 14.89 mg/I to 21.65 mg/I for the period of study.